2022
DOI: 10.3390/molecules27041197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Sterilization Methods on the Microbial and Physicochemical Changes in Prunus mume Juice during Storage

Abstract: This study evaluated the pasteurization (P), ozone (O3), ultrasonic (US), and high-hydrostatic-pressure (HHP) sterilization approaches for processing of Prunus mume regarding browning factors and microorganisms, compared with non-sterilization (control check, CK) treatment. The microorganisms (total bacterial count and fungi and yeast count) in the juice were identified after different sterilization techniques, while the quality parameter changes (degree of browning, color measurements, total phenolic content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…Similar results were also reported in orange [38] and strawberry juice [39] treated with ultrasound. The brightness of noni juice after EZ treatment dropped significantly compared with the CON, which may be due to the enzymatic browning caused by long-time enzymatic treatment and non-enzymatic browning induced by the heating process of enzyme elimination [40] , [22] . Under combined enzymatic and ultrasonic treatment, the greeness of juice sample decreased obviously, while the yellowness increased significantly.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar results were also reported in orange [38] and strawberry juice [39] treated with ultrasound. The brightness of noni juice after EZ treatment dropped significantly compared with the CON, which may be due to the enzymatic browning caused by long-time enzymatic treatment and non-enzymatic browning induced by the heating process of enzyme elimination [40] , [22] . Under combined enzymatic and ultrasonic treatment, the greeness of juice sample decreased obviously, while the yellowness increased significantly.…”
Section: Resultsmentioning
confidence: 93%
“…Subsequently, the absorbance at 625 nm was recorded using a microplate reader (Synergy LX, Biotek, USA). The reducing sugar content was assessed using 3, 5-dinitrosalicylic acid (DNS) method slightly modified from Ma et al [22] . The juice sample or glucose standard solution was added to 200 μL of DNS regent and maintained in boiling water for 5 min, followed by rapid cooling in an ice bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in all juices, TSS was significantly ( p < 0.05) higher after four months storage than at the time of processing. The higher TSS content after heat treatment and storage may be attributed to the hydrolysis of polysaccharides (starch and pectic substances) of juices into monosaccharides and other soluble solids under acidic conditions [ 23 , 24 ]. The results are in agreement with the findings of Khan et al [ 25 ], who reported an increase in the TSS of mango–sea buckthorn blended juices after three months storage.…”
Section: Resultsmentioning
confidence: 99%
“…Chantakun et al [ 6 ] demonstrated that different heat treatment methods, including pasteurization at a high temperature for a shorter time or at a low temperature for a longer time at 118 °C and 121 °C sterilization, had significant effects on the quality and characteristics of bird’s nest beverages. MA et al [ 7 ] reported that different sterilization methods of Prunus mume juice have significant effects on the microbiological and physicochemical parameters, such as the degree of browning, color measurements, total phenolic content, reducing sugar, ascorbic acid, 5-hydroxymethylfurfural, amino acid nitrogen, total soluble solids (TSS), and pH value during storage.…”
Section: Introductionmentioning
confidence: 99%